"Who (Really) is Charlie?" French Cities with Lower Implicit Prejudice toward Arabs Demonstrated Larger Participation Rates in Charlie Hebdo Rallies. Issue 1 (23rd August 2016) - Zerhouni, Oulmann; Rougier, Marine; Muller, Dominique
Following the Charlie Hebdo terrorist attack that happened on January 7 th 2015, around 4 million people gathered all over France in a rally of national unity. Soon, however, critics argued that those who participated to the rallies publicly displayed antiracist attitudes, but were driven by implicit prejudice toward Muslims. Our study addresses the question of whether implicit prejudice measured at the city-level can predict participation rates observed in these cities. We used data from the French/Arab IAT of the Project Implicit collected from 2007 to 2014 on the French territory (n = 3365, 35 cities) and computed mean IAT scores for each city. We then tested whether the IAT scores predicted the participation rate observed in each city. In sharp contrast with the idea that Charlie Hebdo marchers were implicitly biased against Muslims, we found that cities implicitly biased against Arabs (as compared with French) participated less, and not more, to the Charlie Hebdo rallies. These results also show, for the first time, that the level of implicit prejudice measured at the city-level, sometime several years before an event (2007), can predict large scale social behaviors.